2017
DOI: 10.1016/j.tins.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Markers of Motor Inhibition during Human Behavior

Abstract: Transcranial magnetic stimulation (TMS) studies in humans have shown that many behaviors engage processes that suppress excitability within the corticospinal tract. Inhibition of the motor output pathway has been extensively studied in the context of action stopping, where a planned movement needs to be abruptly aborted. Recent TMS work has also revealed markers of motor inhibition during the preparation of movement. Here, we review the evidence for motor inhibition during action stopping and action preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
239
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(276 citation statements)
references
References 149 publications
(201 reference statements)
33
239
3
1
Order By: Relevance
“…This H-reflex presetting in a ''medium state" in non-anticipated perturbations and during stance seems functionally adequate as it may allow immediate up-or down-regulation of the reflex response. It was previously demonstrated that MEPs (Duque et al, 2017) and SICI (Reynolds and Ashby, 1999;Hummel et al, 2009) that were recorded shortly before the onset of nonvoluntary movements (e.g., responses to perturbations) were not modulated (Petersen et al, 2009). Our results -similar SOL MEP-sizes across all three perturbation conditions and during upright stance -are in line with this finding, which suggest that corticospinal excitability was not altered during the preparatory setting.…”
Section: Preparatory Settingsupporting
confidence: 91%
“…This H-reflex presetting in a ''medium state" in non-anticipated perturbations and during stance seems functionally adequate as it may allow immediate up-or down-regulation of the reflex response. It was previously demonstrated that MEPs (Duque et al, 2017) and SICI (Reynolds and Ashby, 1999;Hummel et al, 2009) that were recorded shortly before the onset of nonvoluntary movements (e.g., responses to perturbations) were not modulated (Petersen et al, 2009). Our results -similar SOL MEP-sizes across all three perturbation conditions and during upright stance -are in line with this finding, which suggest that corticospinal excitability was not altered during the preparatory setting.…”
Section: Preparatory Settingsupporting
confidence: 91%
“…35 Moreover, recent TMS studies in humans measuring corticospinal excitability observed preparatory inhibition, consistent with the broad suppressive effect by the STN. 43 Thus, the relative RT speeding on conflict trials in the Ready period that we observed for stimulation might fit this ‘clearing alternatives’ view. Moreover, this RT speeding in the absence of any impact on errors suggests that Ready stimulation may have improved performance.…”
Section: Discussionmentioning
confidence: 63%
“…; Duque et al . ; Massé‐Alarie et al . ), suggesting the existence of different mechanisms between these two processes.…”
Section: Discussionmentioning
confidence: 99%